2022
DOI: 10.1038/s41598-022-08791-z
|View full text |Cite|
|
Sign up to set email alerts
|

Thioredoxin interacting protein protects mice from fasting induced liver steatosis by activating ER stress and its downstream signaling pathways

Abstract: Under normal conditions, fasting results in decreased protein disulfide isomerase (PDI) activity and accumulation of unfolded proteins, leading to the subsequent activation of the unfolded protein response (UPR)/autophagy signaling pathway to eliminate damaged mitochondria. Fasting also induces upregulation of thioredoxin-interacting protein (TXNIP) expression and mice deficient of this protein (TXNIP-KO mice) was shown to develop severe hypoglycemia, hyperlipidemia and liver steatosis (LS). In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…A reduction in aortic TXNIP expression levels increased TRX expression levels, leading to the ablation of NADPH oxidase expression 21 , which protected against endothelial dysfunction induced by several disorders. Research on diabetes-related mouse models has demonstrated the generation of oxidative stress and excessive ROS production due to the ablation of TRX activity by TXNIP 23 . In addition, TXNIP regulates the production of ROS through mitochondria and NADPH oxidase under high glucose conditions 23 , 24 .…”
Section: Multiple Functions Of Txnip In the Cellular Stress Response ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in aortic TXNIP expression levels increased TRX expression levels, leading to the ablation of NADPH oxidase expression 21 , which protected against endothelial dysfunction induced by several disorders. Research on diabetes-related mouse models has demonstrated the generation of oxidative stress and excessive ROS production due to the ablation of TRX activity by TXNIP 23 . In addition, TXNIP regulates the production of ROS through mitochondria and NADPH oxidase under high glucose conditions 23 , 24 .…”
Section: Multiple Functions Of Txnip In the Cellular Stress Response ...mentioning
confidence: 99%
“…Research on diabetes-related mouse models has demonstrated the generation of oxidative stress and excessive ROS production due to the ablation of TRX activity by TXNIP 23 . In addition, TXNIP regulates the production of ROS through mitochondria and NADPH oxidase under high glucose conditions 23 , 24 . These findings demonstrate two-way negative feedback between ROS and TXNIP, and reduced TRX acts as an intermediate 20 .…”
Section: Multiple Functions Of Txnip In the Cellular Stress Response ...mentioning
confidence: 99%